A assistência social e as oligarquias em pequenos municípios do sertão paraibano - Eduardo, Gabriela Nogueira (2015)
In the backlands of Paraiba, there is a tradition of oligarchies that take power for many years in the halls in small towns. Social assistance has expanded in the last ten years throughout the national territory. We argue in the text that social assistance contributes to reproduction of the oligarchies in small municipalities in the backwoods of Paraiba. Our main objective refers to examine to what extent the social assistance policy contributes to the reproduction of the power of the oligarchs in the municipalities that make up the backlands of Paraiba. The specific objectives are to know the political and economic determinations of the Paraíba Wilderness located at a regional and national context; Knowing the basics, legislation and the implementation of the Social Assistance Policy in the backlands of Paraiba; And identify the extent to which social assistance policy reiterates the power relations in the backlands of Paraiba. The locus of the research were the municipalities of Cachoeira dos Indios, Marizópolis, Paulista and Mount Horeb. The methodology used it comes to the orientation of the Marxist method. The first procedure was reading and BOOK REPORT on the political, cultural and social of the Paraíba Hinterland. The second was the realization of a documentary research on the plans, programs and projects implemented in the context of social assistance. The third was the application of a questionnaire with the users of Social Assistance Reference Centres (CRAS) in the municipalities of São Paulo, Mount Horeb, Marizópolis and Waterfall Indians. The work is divided into three main chapters. The first chapter deals with the foundations of the state, and historical notes about the backwoods of Paraiba. The second chapter deals with the capital x labor conflict and social assistance as well as programs and projects being implemented in the backlands of Paraiba and the third analyzes the results of the research. We conclude that social assistance contributes to the reproduction of the power of the oligarchy through the gratitude of the people who influence voting in them. And because social assistance have emerged and developed, with the function conform the population facing manifestations social inequality, thus ensuring the reproduction of exploitation in the production process, thus acting in the aftermath of Social Issues. Therefore, it is necessary to invest in the struggle of the working class and its political articulation. Legitimize a law prohibiting that large companies invest in the political campaign and make unfair competition to anyone working class applying for any political office. With regard to rural workers is necessary to fight the appreciation of the farmer and Agrarian Reform, by the end of the drought industry and landlordism.